Sequential application of vacuum sealing drainage and antibiotic-loaded bone cement for the successful treatment of a diabetic ischemic foot ulcer: a case report - Feng, Xia; Ma, Chao; Zhang, Zhihui; Xu, Lei; Fang, Yudong (Frontiers in Endocrinology, 2026)
BackgroundDiabetic foot ulcers (DFUs), particularly those with ischemic components, present a major therapeutic challenge due to poor perfusion, high infection risk, and delayed wound healing. Conventional treatments often fail to achieve satisfactory outcomes in complex cases. Vacuum sealing drainage (VSD) has shown promise in wound healing by enhancing angiogenesis, stimulating granulation tissue formation, and reducing bacterial colonization while antibiotic-loaded bone cement (ALBC) offers localized, high-concentration antimicrobial delivery. However, the sequential application of these two modalities is rarely reported in ischemic DFUs.Case presentationWe report the case of a 78-year-old female with type 2 diabetes mellitus who presented with a chronic, infected, ischemic foot ulcer that was unresponsive to standard wound care and systemic antibiotics. Surgical debridement was performed, followed by the application of VSD to enhance granulation tissue formation and maintain negative pressure drainage. Antibiotic-loaded bone cement was subsequently applied to fill the wound cavity and control local infection. Over the subsequent weeks, sequential application of VSD and ALBC resulted in remarkable improvement of the ulcer, ultimately achieving complete wound healing without the need for revascularization or major amputation.ConclusionThis case demonstrates that the sequential application of VSD and ALBC may offer a synergistic therapeutic strategy for the management of complex diabetic ischemic ulcers. This approach may provide an effective alternative in cases where infection control and wound healing are otherwise difficult to achieve.